The Pochonia chlamydosporia Serine Protease Gene vcp1 Is Subject to Regulation by Carbon, Nitrogen and pH: Implications for Nematode Biocontrol - Ward, Elaine; Kerry, Brian R.; Manzanilla-López, Rosa H.; Mutua, Gerald; Devonshire, Jean; Kimenju, John; Hirsch, Penny R. (PLOS ONE, 2012)
The alkaline serine protease VCP1 of the fungus Pochonia chlamydosporia belongs to a family of subtilisin-like enzymes that are involved in infection of nematode and insect hosts. It is involved early in the infection process, removing the outer proteinaceous vitelline membrane of nematode eggs. Little is known about the regulation of this gene, even though an understanding of how nutrients and other factors affect its expression is critical for ensuring its efficacy as a biocontrol agent. This paper provides new information on the regulation of vcp1 expression. Sequence analysis of the upstream regulatory region of this gene in 30 isolates revealed that it was highly conserved and contained sequence motifs characteristic of genes that are subject to carbon, nitrogen and pH-regulation. Expression studies, monitoring enzyme activity and mRNA, confirmed that these factors affect VCP1 production. As expected, glucose reduced VCP1 expression and for a few hours so did ammonium chloride. Surprisingly, however, by 24 h VCP1 levels were increased in the presence of ammonium chloride for most isolates. Ambient pH also regulated VCP1 expression, with most isolates producing more VCP1 under alkaline conditions. There were some differences in the response of one isolate with a distinctive upstream sequence including a variant regulatory-motif profile. Cryo-scanning electron microscopy studies indicated that the presence of nematode eggs stimulates VCP1 production by P. chlamydosporia, but only where the two are in close contact. Overall, the results indicate that readily-metabolisable carbon sources and unfavourable pH in the rhizosphere/egg-mass environment may compromise nematode parasitism by P. chlamydosporia. However, contrary to previous indications using other nematophagous and entomopathogenic fungi, ammonium nitrate (e.g. from fertilizers) may enhance biocontrol potential in some circumstances.